On rare for the Primorye waters species of mackerel Scomberomorus niphonius (Cuvier, 1832) - Vladimir N. Dolganov (Известия ТИНРО, 2016)
Description of the mackerel Scomberomorus niphonius caught in the Vityaz Bay (Peter the Great Bay, Japan Sea) on September 19, 2015.